Community dynamics influencing commercial tobacco control policy development on California American Indian lands: a qualitative analysis of baseline CAITIE data - Wiebe-Anderson, Jeremiah; Lippert, Danielle R.; Al-Delaimy, Wael K. (Frontiers in Public Health, 2025)
IntroductionCommercial tobacco control policies are credited with substantially decreasing the rates of commercial tobacco use among the general US population over the last few decades, yet determining the attitudes, values and beliefs that make such policies more or less appropriate for American Indian communities remains of great interest in efforts to address tobacco-related health disparities.MethodsThrough the qualitative analysis of 57 baseline interviews conducted by the CAITIE project in 2021 and 2022, we explain and explore community dynamics that favor or oppose new commercial tobacco control policies in California American Indian communities.ResultsThe community dynamics that favor new policies include themes of changing social norms and the influence of Tribal leadership. The community dynamics that oppose new policies include respect for autonomy, preference for ‘small-p’ policies, and concern for lost revenue.DiscussionAn understanding of these community dynamics may help to inform more fruitful efforts to address commercial tobacco use both within Tribal communities and in partnerships between Natives and non-Natives.